Creation of physiologic rhythm by closed loop stimulation in heart failure patients with severe chronotropic incompetence: worldwide first results of a pilot study. (25th November 2020) - Proff, J; Merkely, B; Papp, R; Lenz, C; Nordbeck, P.J; Butter, C.H; Meyerhoefer, J; MacCarter, D; Thouet, T.H; Roser, M
Abstract: Background: The prevalence of chronotropic incompetence (CI) in heart failure (HF) population is high and negatively impacts prognosis. In HF patients with an implanted cardiac resynchronisation therapy (CRT) device and severe CI, the effect of rate adaptive pacing on patient outcomes is unclear. Closed loop stimulation (CLS) based on cardiac impedance measurement may be an optimal method of heart rate adaptation according to metabolic need in HF patients with severe CI. Purpose: This is the first study evaluating the effect of CLS on the established prognostic parameters assessed by the cardio-pulmonary exercise (CPX) testing and on quality of life (QoL) of the patients. Methods: A randomised, controlled, double-blind and crossover pilot study has been performed in CRT patients with severe CI defined as the inability to achieve 70% of the age-predicted maximum heart rate (APMHR). After baseline assessment, patients were randomised to either DDD-CLS pacing (group 1) or DDD pacing at 40 bpm (group 2) for a 1-month period, followed by crossover for another month. At baseline and at 1- and 2-month follow-ups, a CPX was performed and QoL was assessed using the EQ-5D-5L questionnaire. The main endpoints were the effect of CLS on ventilatory efficiency (VE) slope (evaluated by an independent CPX expert), the responder rate defined as an improvement (decrease) of the VE slope by at least 5%, percentage of maximal predicted heart rate reserve (HRR) achieved, and QoL. Results: Of the 36 patients enrolled in the study, 20 fulfilled the criterion for severe CI and entered the study follow-up (mean age 68.9±7.4 years, 70% men, LVEF=41.8±9.3%, 40%/60% NYHA class II/III). Full baseline and follow-up datasets were obtained in 17 patients. The mean VE slope and HRR at baseline were 34.4±4.4 and 49.6±23.8%, respectively, in group 1 (n=7) and 34.5±12.2 and 54.2±16.1% in group 2 (n=10). After completing the 2-month CPX, the mean difference between DDD-CLS and DDD-40 modes was −2.4±8.3 (group 1) and −1.2±3.5 (group 2) for VE slope, and 17.1±15.5% (group 1) and 8.7±18.8% (group 2) for HRR. Altogether, VE slope improved by −1.8±2.95 (p=0.31) in DDD-CLS versus DDD-40, and HRR improved by 12.9±8.8% (p=0.01). The VE slope decreased by ≥5% in 47% of patients ("responders to CLS"). The mean difference in the QoL between DDD-CLS and DDD-40 was 0.16±0.25 in group 1 and −0.01±0.05 in group 2, resulting in an overall increase by 0.08±0.08 in the DDD-CLS mode (p=0.13). Conclusion: First results of the evaluation of the effectiveness of CLS in CRT patients with severe CI revealed that CLS generated an overall positive effect on well-established surrogate parameters for prognosis. About one half of the patients showed CLS response in terms of improved VE slope. In addition, CLS improved quality of life. Further clinical research is needed to identify predictors that can increase the responder rate and to confirm improvement in clinical outcomes. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Biotronik SE & Co. KG